Dexmedetomidine Attenuates Cellular Injury and Apoptosis in H9c2 Cardiomyocytes by Regulating p-38MAPK and Endoplasmic Reticulum Stress - Zhu Z; Ling X; Zhou H; Zhang C; Yan W (Dove Medical Press, 2020)
Zhipeng Zhu,1,* Xiaoyan Ling,2,* Hongmei Zhou,1 Caijun Zhang,1 Weiwei Yan1 1Department of Anesthesiology, The Second Affiliated Hospital of Jiaxing University, Jiaxing City, Zhejiang Province 314000, People’s Republic of China; 2The Outpatient Nursing Department of the Second Affiliated Hospital of Jiaxing University, Jiaxing City, Zhejiang Province 314000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Zhipeng ZhuDepartment of Anesthesiology and Pain, The Second Affiliated Hospital of Jiaxing University, Jiaxing City, Zhejiang Province, People’s Republic of ChinaEmail xiaozhu781126@163.comBackground: Myocardial ischaemia-reperfusion injury (IRI) has been confirmed to induce endoplasmic reticulum stress (ERS) when myocardial cell function continues to deteriorate to a certain degree. The clinical applications of effective tested strategies are sometimes inconsistent with the applications evaluated in experiments, although reasonable mechanisms and diverse signalling pathways have been broadly explored. Dexmedetomidine (DEX) has been shown to attenuate IRI of the heart in animal studies. This study aimed to determine whether DEX can protect injured cardiomyocytes under hypoxia/reoxygenation (H/R) at the cellular level and whether the mechanism is related to ERS and the p38 MAPK pathway.Methods: H9c2 cells were subjected to H/R or thapsigargin (TG) to build a model. DEX or 4-PBA was added to the medium either 1 h or 24 h before modelling, respectively. Model parameters were determined by assessing cell viability and injury, which were measured by assessing cell counting kit-8 (CCK8), lactate dehydrogenase (LDH) release and ﬂow cytometry results, and the expression of GRP78, CHOP and caspase-12. In addition, the protein expression of p38MAPK and p-p38MAPK was examined, and SB202190, a negative regulator, was also preincubated in medium.Results: Compared to that of cells in the control group, the activity of cells in the H/R and TG groups was decreased dramatically, and the LDH concentration and proportion of apoptotic cells were increased. DEX could correspondingly reverse the changes induced by H/R or TG. Additionally, DEX effectively attenuated ERS defined as increased expression of GRP78, CHOP and caspase-12. Additionally, DEX could obviously depress the P38 MAPK phosphorylation and high p-p38 MAPK expression in the TG group, indicating DEX has a function similar to that of SB202190.Conclusion: H/R injury in H9c2 cells can lead to abnormal ERS and apoptosis, as well as activation of the p38MAPK signalling pathway. DEX can protect cardiomyocytes by intervening in ERS, regulating p38MAPK and the downstream apoptotic signalling pathway.Keywords: dexmedetomidine, hypoxia/reoxygenation injury, endoplasmic reticulum stress signalling pathway, p38 mitogen-activated protein kinase